(untitled) (Experimental biology, 2009)
In experiments on rats it was shown that the animals with the “strong” type of higher nervous activity had more erythrocytes membrane resistance level. Moreover, “Uragan-forte” herbicide decreased erythrocyte membrane resistance in hypo- and hypertonic NaCl and saccharose solutions, and the erythrocyte membrane structural protein spectrine plays a special role in this process.